A PENYULUHAN CARA PENGGUNAAN DAN JENIS-JENIS OBAT CACING DI POSYANDU PERUMAHAN PATEBON INDAH KABUPATEN KENDAL - elvira rosa; Haini Santi; Megananda; Auliya Arifyani; Dewi Nilawati (JURNAL ABDIMAS DOSMA (JAD), 2022)
Residential mothers there are still Patebon Indah Kendal who do not understand how to use and the types of deworming medicine that can be used for children. The main activities in PkM lecturers include drug introduction training and counseling on the treatment of intestinal worms for children. Activities in the training included introducing mothers to how to use and types of deworming drugs on the market. With the PkM activity training, lecturers are believed to be able to increase public knowledge about the use of deworming drugs for children.